PENGELOLAAN ZAKAT DALAM TINJAUAN UU RI NO. 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - muh ruslan abdullah (Al-Amwal : Journal of Islamic Economic Law, 2018)
Based on data obtained from BAZNAS, Indonesia has a zakat potential of 217 trillion per year, but its realization is only about Rp 6 trillion per year. This condition requires the government to think about how to effectively increase the collection of zakat. One of the strategic steps taken by the government is to issue Law No. 23 of 2011 on the Management of Zakat. However, the law has not been able to maximize the performance of BAZNAS/LAZ and persuade people to pay zakat. On the contrary, Law No. RI. 23 of 2014 Regarding local governance can improve the management of zakat in BAZNAS, and sanction against muzakki who do not give the zakat.